Exploring culturally sustaining practice for indigenous learners in initial teacher education in Aotearoa New Zealand - Robin Averill; Hiria McRae (Universidade Federal do Oeste da Bahia, 2020)
Culturally sustaining practices are advocated for enhancing learning experiences of Indigenous learners. Developing the use of culturally sustaining practice is challenging, in part as many educators do not have Indigenous heritage and have not themselves experienced such teaching. Here we discuss an investigation into how we develop student teacher understanding of practice culturally sustaining for Indigenous Māori learners in our initial mathematics teacher education courses. We show how a four-dimension framework (accommodation, reformation, transformation, and representation) can expose strengths and opportunities for improvement in course content and approaches towards developing culturally sustaining practices. Factors considered include education policy, resources, course development and content. Affordances (e.g., ease of use) and challenges (e.g., contextal factors) of using the framework are discussed. We demonstrate that the framework can be a useful tool for teacher educators working to strengthen their focus on developing culturally sustaining teacher practice to enhance educational opportunities of Indigenous learners.